The high-frequency application of double-barrier resonant tunnelling diodes - Steenson, David Paul (1993)
The aim of this Thesis was to try to develop an understanding of the growth and fabrication of Double Barrier Resonant Tunnelling (DBRT) diodes, in order to enhance their properties at millimetre wave frequencies (ie. above 35GHz). Chapter 1 introduces the DBRT diode and outlines some of its applications while Chapter 2 describes aspects of device fabrication. Chapter 3 discusses the solid-state and quantum mechanical aspects which determine the DBRT's current-voltage characteristics and Chapter 4 describes an extensive parametric study relating the device properties to the high frequency behaviour. Chapter 5 covers the applications of DBRT devices at high frequencies and presents some of the results achieved so far.